DAMPAK PENGGUNAAN MEDIA VISUAL DALAM PEMBINAAN IMAN CALON KOMUNI PERTAMA DI PAROKI ST. SIMON PETRUS TARUS KEUSKUPAN AGUNG KUPANG - Hayon, Vinsensius; Leu, Lorensius (Selidik (Jurnal Seputar Penelitian Pendidikan Keagamaan), 2021)
This study aims to examine and analyze the impact of using visual media in faith-building and the effectiveness of the application of visual media for mentoring the candidate of the first communion at St. Parish. Simon Peter Tarus. The type of research used is action research with a descriptive method that describe the factors that are the source of strengths and successes as well as weaknesses or obstacles to the implementation of faith-building: are these factors related to the training material; the means and methods of presenting the material, the discipline factor and the attendance of the coaching participant, the participation of the participant, or due to another factor. The result showed that using the visual media method had a very positive impact. This is indicated by the results of the study, that the increase in the result of coaching/learning participants with a success rate of 75% of participants got a score of 75 as measured by test question at the end of the cycle. Based on the test result obtained by the participant at the end of each cycle, it showed an increase in the result of faith development with an achievement value of 100% (end of cycle II).